Molecular phylogeography of Echis carinatus revisited: Insights from the Sri Lankan population of saw-scaled viper (Serpentes: Viperidae: Echis) - Murugananthan, A.; Gnanathasan, A.; Kumanan, T.; Amarasinghe, K.P.; Pirasath, S. (National Science Foundation of Sri Lanka, 2025)
The saw-scaled viper (Echis carinatus) is a member of the Viperidae family, known for its intricate taxonomic history. Initially, it was believed to be a unique Sri Lankan subspecies called E. c. sinhaleyus. The subsequent clinical evidence also suggests the presence of a distinct subspecies in Sri Lanka. However, its existence was later questioned, urging the need for genetic studies. Therefore, it was aimed to unravel the molecular phylogenetic affinities of the Sri Lankan population of E. carinatus. For the first time, the molecular phylogenetic affinities and phylogeography of the Sri Lankan population of E. carinatus were explored. This study was based on sequences of samples obtained from 12 locations across the Northern Province, using mitochondrial markers Cytb, NADH4, 16S, and 12S. Molecular phylogenetic analyses showed that the South Indian and Sri Lankan populations of E. carinatus form a reciprocally monophyletic clade, which is recovered as the sister group to the remaining groups of E. carinatus. Based on the divergence-time estimates, the divergence between Sri Lankan and South Indian population of E. carinatus is estimated to have occurred in the mid Pleistocene epoch. This study discloses that E. carinatus comprises two distinct subspecies namely, E. c. carinatus and E. c. sochureki. The Sri Lankan and South Indian populations belong to the subspecies E. c. carinatus, whereas E. c. sochureki comprises the remaining populations of E. carinatus distributed across northern, western, and eastern India (Rajasthan, Maharashtra, Odisha, and Goa), as well as in Pakistan, Sharjah, and Iraq.
Keywords: Biogeography; Mitochondrial markers; Molecular phylogeny; Snakes; Vipers